MULTIKULTURALISME DAN HEGEMONI POLITIK PERNIKAHAN ENDOGAMI: IMPLIKASI DALAM DAKWAH ISLAM - Syarifah Ema Rahmaniah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This paper described a variety of views on the dynamics of endogamy marriage practiced by sharif community in Pontianak. This paper used the theory of hegemony to analyze Surah al-Ahzab: 33 as the cause of endogamy among the descendants of 'Isa al-Muhajir (Ba ‘Alawi) that have migrated to the archipelago. One of her off spring grew and spread in Pontianak was called sharif or syarifah of Pontianak. The results of this study explained that there are three different attitudes about endogamous marriage, they are accept, reject and moderate thinking. The three different attitudes came out as the result of modernization, contact with foreign cultures, the influence of education, socio-economic, and the existing settlement pattern. There is a socio-political implications of the verses of hegemony that is keeping the values of the potential political kinship as social capital to raise awareness and political culture in the context of community participation and representation of sharif in local and national politics. But in sociocultural context. Once endogamy was understood as an absolute system that must be run so it may open space of social stratification that threatens women’s freedom and will open the spaces for subordination.